Ictiofauna de Água Doce da Bacia do Rio Parnaíba - Ramos, Telton Pedro Anselmo (2012)
The Parnaíba River is the longest river in Northeast Brazil, with its drainage extending completely inside this region. It is one of the few perennial rivers in the Brazilian Northeast Region, running predominantly in the area of Caatinga on the east (with intermittent drainages associated to this type of environment), and partly extending in the Cerrado region on the west; the river is 1400 km long with its hydrographic basin occupying an area of 344,112 km2 (3.9% of Brazilian territory) and draining almost the entire state of Piauí (99%), part of Maranhão state (19%) and Ceará state (10%). The objective of this project was to describe the diversity of freshwater fishes of the Parnaíba river basin by: conducting a comprehensive ichthyofaunal inventory of the basin;; the description of possible new species identified in the survey; the study of the composition, diversity, richness and abundance of fish fauna through the High, Medium and Low portions of main course Parnaíba River, and the evaluation of their relationships with hydrologic disturbances of the environment; the record of the presence of rare species, in order to contribute to the development of conservation policies for the sustainability of aquatic biota in the region; the development of a handbook on the fish fauna of the Parnaíba river basin. The sampling design of this project was based on the establishment of (1) fixed points for seasonal collection (dry and wet season, two years) in three portions of the main course of Parnaíba River, called Regular Points (nine groups of three points, totaling 27 sites), (2) "Aquarap" protocol collections which covered the entire basin and (3) carefully critical analysis of the information on fish fauna registered in the literature as occurring in the basin. The collection effort amounted to 244 surveyed sampling sites along the basin. Samples were collected along the years 2008 to 2011. Fish were collected with the use of trawl nets, cast nets, gill nets and dip nets; only the first two fishing gears were used in Regular Points. As a result, was recorded 143 species of freshwater fish in the Parnaíba river basin, distributed in 101 genera, 33 families and 11 orders. Among these species, 23 are new records for the basin, 25 are undescribed species, eight were recorded only from the literature (not collected in this study) and seven are exotic species. The recorded number of 143 species surpasses in more than 40 the previous assumptions on the richness of freshwater fishes of the Parnaíba river basin, reported in literature. Fifty endemic species were recorded, corresponding to 36.8% of the 136 native species recorded in the present study, this number representing an increase of 30 species related to the largest number proposed by previous authors. From these 136 native species, 41 (30.1%) were shared with the Amazon basin, 11 (8.1%) with the Middle- Eastern Northeast Region (Nordeste Médio-Oriental), and other 11 (8.1%) with the San Francisco basin. These data suggest that the fish fauna of the Parnaíba river basin, based on similarity of species, is closer to that of the Amazon basin than to the fish fauna from other basins or groups of basins analyzed. The survey conducted along the Regular Points on High, Medium and Low showed that: the High portion was that with the highest abundance was recorded, followed by Lower portion and, finally, by the Middle one; collections during wet season resulted in greater abundance; also in higher average of richness and diversity of species in all the three portions of the basin were recorded during this season; when considered the average of richness and diversity, the Lower portion was the that with the high average of richness, followed by the Upper and Middle portions; diversity did not follow the pattern of richness due to the number of rare species in the three portions of the river, the low portion recorded as that of high diversity.